Prognostic biomarkers for immunotherapy in esophageal cancer - Tong, Xu; Jin, Meiyuan; Wang, Lulu; Zhang, Dongli; Yin, Yuping; Shen, Qian (Frontiers in Immunology, 2024)
Esophageal cancer (EC), a common type of malignant tumor in the world, ranks as the sixth highest contributor to cancer-related mortality worldwide. Due to the condition that most patients with ECthe majority of EC patients are diagnosed at advanced or metastatic status, the efficacy of conventional treatments including surgery, chemotherapy and radiotherapy is limited, resulting in a gloomy dismal 5-year overall survival (OS) rate. In recent years, the application of immune checkpoint inhibitors (ICIs) has presented a novel therapeutic avenue for EC patients.Currently, bBoth ICIs monotherapy and immunotherapy combined with chemotherapy or chemoradiotherapy (CRT) have demonstrated marked benefits for patients with advanced EC. In the realm of perioperative treatment pattern, aAdjuvant or neoadjuvant therapy incorporating immunotherapy has also demonstrated displayed promising prospects in the context of perioperative treatment. Nonetheless, due to the variable response observed among patients undergoing immunotherapy, it is of vital importance to identify predictive biomarkers for stratifying patient stratifications, to facilitate identification of in order to recognize the subgroups who may derive greater benefits from immunotherapy. In this review, we summarize validated or potential biomarkers for immunotherapy in EC from in three dimensions: tumor-cell-associated biomarkers, tumor-immune microenvironment (TIME)-associated factors, and host-associated biomarkers, so as to provide a theoretical foundation to inform tailored therapy for individuals diagnosed with EC.